Density Functional Theory Calculations for Diaminonaphthalene Molecules group - Mohi, Ali Taher (University of Thi-Qar Journal of Science, 2014)
Theoretical studies for calculating molecular structure parameters of naphthalene and its simplest derivatives with electron-donating groups (di-amino) in different positions were performed using density functional theory (DFT). Based on B3LYP with 6-31(d,p) basis set was used to investigate the effect on the electronic and structure properties for the positional variation of the amino substituents in the naphthalene. The optimized structures, total energies, electronic states, energy gaps, ionization potentials, electron affinities, chemical potential, global hardness, softness, global electrophilictity, dipole moment and dipole polarizability were calculated. The harmonic vibrational frequencies calculated and compared with available experimental data. The results showed a decrease in energy gaps and the presence of the electron-donating groups leads to easy oxidation.